The Journey Metaphor’s Entailments for Framing Learning - Bradley Smith (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
Analysis of differing frames for learning to write shows that the journey metaphor best serves our efforts to convey how writing and learning are linked.